Primary Adult Renal Ewing's Sarcoma: A Rare Entity. (2nd April 2009) - Mukkunda, Ravindra; Venkitaraman, Ramachandran; Thway, Khin; Min, Toon; Fisher, Cyril; Horwich, Alan; Judson, Ian
Abstract : Background . Ewing's sarcoma of extraskeletal origin is uncommon and that is of primary renal origin in adults are rare. There is no consensus on the optimal management of Ewing's tumors of renal origin. Methods . A retrospective review of the clinical features, treatment, and outcome of adult patients with primary renal extra-skeletal Ewing's sarcoma who were treated at the Royal Marsden hospital from January 1993–December 2007 is reported. Results . Seven adult patients with primary renal Ewing's sarcoma were identified. All four patients with nonmetastatic disease had radical nephrectomy and received adjuvant chemotherapy +/− radiotherapy. Two developed metastatic disease while on adjuvant chemotherapy, and one patient relapsed after 55 months. The three patients with metastatic disease at presentation did not have nephrectomy and were treated with chemotherapy. All three patients had disease progression with a dismal outcome. Only one patient in the whole group is alive and disease free. The median overall survival was 62.8 months, and the median disease-free survival in patients with nonmetastatic disease after combined modality treatment was 30.3 months. Conclusion . Primary adult renal Ewing's sarcoma is an aggressive tumor with a propensity for early metastasis. Radical nephrectomy with adjuvant combination chemotherapy produced the best results but the outlook remained poor with only one patient experiencing long disease-free survival.